First neutrino observations from the sudbury neutrino observatory - McDonald, AB; Boulay, MG; Bonvin, E; Chen, M; Duncan, F; Earle, E; Evans, H; Ewan, G; Ford, R; Hallin, A; Harvey, P; Hepburn, J; et al. (2000)
The first neutrino observations from the Sudbury Neutrino Observatory are presented from preliminary analyses. Based on energy, direction and location, the data in the region of interest appear to be dominated by 8B solar neutrinos, detected by the charged current reaction on deuterium and elastic scattering from electrons, with very little background. Measurements of radioactive backgrounds indicate that the measurement of all active neutrino types via the neutral current reaction on deuterium will be possible with small systematic uncertainties. Quantitative results for the fluxes observed with these reactions will be provided when further calibrations have been completed.